Folliculotropic mycosis fungoides: clinical and histologic features in five patients - Amir Hooshang Ehsani; Arghavan Azizpour; Pedram Noormohammadpoor; Hasan Seirafi; Farshad Farnaghi; Kambiz Kamyab-Hesari; Mehdi Sharifi; Maryam Nasimi (Wolters Kluwer Medknow Publications, 2016)
Background: Alopecia can be a manifestation of mycosis fungoides (MF); however, the prevalence is unknown. Aims: We sought to describe the clinicopathologic presentation of alopecia in patients with diagnosis of MF. Methods: A retrospective analysis of patients with biopsy-proven MF, who were evaluated at our cancer center from 2002 to 2012, was performed to identify patients with alopecia. Results: Five patients with alopecia were identified from reviewing of 157 patients with MF. The male:female ratio was 3:2, and the mean age of patients was 42.8 years. Two of these patients showed patchy hair loss on scalp which was clinically identical to alopecia areata. In remaining three patients, hair loss was seen in areas of MF lesions, and epidermal changes consisted of patch- and plaque-type lesions of MF, tumors, and follicular lesions (follicular MF) were also present. In two of these patients, lymphadenopathy without any visceral involvement was detected. Conclusions: Alopecia was observed in 5 (3.18%) patients with MF, which makes it a rare finding, which included alopecia areata-like patchy loss in 2 and alopecia within MF lesions in 3.